A Christmas in the Alps - Carlson, Melody (Revell, a division of Baker Publishing Group, 2021)
"When Simone Winthrop discovers a letter from her great-grandmother hinting that she's heir to a family treasure, she travels to France at Christmastime to stake her claim. With the help of a charming clockmaker she meets along the way, she just may uncover the truth behind this mysterious inheritance . . . and a bit more she hadn't bargained for"--